THE EU REGULATORY ACTIVITIES IN THE AREA OF DIGITAL PLATFORMS AND SERVICES PROVISION (EU and comparative law issues and challenges series (ECLIC), 2021)
New and innovative ways of service provisions based on digital platforms have changed the ways in which doing business, communicating and connecting providers to users in the EU Internal Market are shaped and transformed. Since the adoption of the Directive 2000/31/EC (the E-Commerce Directive) in 2000 digital services have gained market dominance, and this has become especially evident during the Covid-19 virus crisis when the importance of digital technologies in all aspects of modern life became prominent. It has clearly shown the dependency of the economy and the society on digital services highlighting both the benefits and the risks that stem from the current framework for the functioning of the services provided by the digital platforms regardless of whether they are defined as digital services or not. In the European Commission (EC) Communication “Shaping Europe’s Digital Future” the EC committed to update the horizontal rules that define the responsibilities and obligations of digital service providers, and online platforms in particular. Additionally, the European Parliament’s “Report on the Digital Services Act and fundamental rights issues posed” highlights the need for legal clarity of platforms and users, as well as respect for fundamental rights in the light of the rapid development of technology. According to the current data, the digital platforms account for over 10% of the EU's 45 million users. These platforms are subject not only to the specific obligations in controlling their own risks, but also to a new oversight structure. In 2020 the EC initiative was finalized by the “Proposal for a Regulation on a Single Market for Digital Service” which addresses the negative consequences arising from certain behaviours on platforms. Since the EU Internal market is impacted significantly by platforms that serve as intermediaries for business users to reach their customers, sometimes these companies assume control over the entire platform ecosystems, which in turn can grant them the opportunity to regulate certain relations. The controlling power comes from the practices that platform companies exercise and from using the data of the businesses and users operating on these platforms. This paper aims to analyse the current regulation on digital platforms and digital service provisions in the EU Internal Market and offer some conclusions on its possible impact on the market’s functioning especially in the times of the Covid-19 pandemic and subsequently.